A representative and comprehensive review of the electrical and thermal properties of polymer composites with carbon nanotube and other nanoparticle fillers. Issue 9 (17th May 2017) - Jouni, Mohammad; Djurado, David; Massardier, Valérie; Boiteux, Gisèle
Abstract: In this review we present the results of our literature investigation into the electrical and thermal properties of carbon nanotube polymer composites. A short selection of data relating to conductive polymer composites with various fillers is provided for comparison. The effects of filler properties such as type and size, the use of hybrid fillers, fabrication methods for polymer composites and the importance of the modeling of the electronic and thermal transport mechanisms are discussed, as are more general factors influencing the properties of these composites. This review represents a comprehensive survey and constructive study and should serve as a useful reference tool for industrial and academic researchers working in this field. © 2017 Society of Chemical Industry Abstract : It has been proved from both theoretical and experimental viewpoints that the electrical and thermal properties in conductive polymer composites depend on many parameters such as the type of matrix, the fabrication method, the nature and size of the filler (as an example the influence of the aspect ratio on the electrical percolation) etc. In this context, we give an overview of the influence of these obvious parameters. However, we pay particular attention to show how other factors less discussed in the literature are affecting these properties.